Correlation of 16S Ribosomal DNA Signature Sequences with Temperature-Dependent Growth Rates of Mesophilic and Psychrotolerant Strains of the Bacillus cereus Group - Prüß, Birgit M. (American Society for Microbiology, 1999)
Sequences of the 16S ribosomal DNA (rDNA) from psychrotolerant and mesophilic strains of the Bacillus cereus group revealed signatures which were specific for these two thermal groups of bacteria. Further analysis of the genomic DNA from a wide range of food and soil isolates showed that B. cereus group strains have between 6 and 10 copies of 16S rDNA. Moreover, a number of these environmental strains have both rDNA operons with psychrotolerant signatures and rDNA operons with mesophilic signatures. The ability of these isolates to grow at low temperatures correlates with the prevalence of rDNA operons with psychrotolerant signatures, indicating specific nucleotides within the 16S rRNA to play a role in psychrotolerance.